ANALYSIS OF STRENGTHS, WEAKNESSES, OPPORTUNITIES, THREATS (SWOT) ON BUSINESS DEVELOPMENT (CASE STUDY ON NYOKAP PEMPEK) - Dianka Wahyuningtias; Daniel Chung (Jurnal Industri Parawisata, 2022)
This research is motivated by the decline in product sales at Pempek Nyokap since the Covid-19 pandemic. Consumers become more careful in buying goods, especially food, considering that the quality of products, services, and packaging are considered by consumers before buying a product. The method used in this study is a qualitative method by conducting observations, interviews, and Focus Group Discussions on the sample at Pempek Nyokap. The data analysis technique used is EFAS, IFAS, IE, and SWOT Matrix. The final results achieved in the study indicate that business strategies can be implemented for the business development of Pempek Nyokap. The strategy is in the form of opening an offline store, opening a stall in the marketplace, collaborating with online delivery services, and conducting promotions through promoters.